Improvement of The Physical Properties of Rainfed Rice Soil in Sungai Rakyat Village, Panai Tengah Sub-District, Labuhanbatu District by Utilizing Municipal Waste into Compost - Syarifa Mayly; Harahap FS (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Utilization of organic matter is one very big step in increasing soil fertility and will determine soil productivity. The role of organic matter does not only play a role in providing plant nutrients but is far more important in improving the physical, chemical, and biological properties of the soil. This is very related that through the application of organic matter, efforts can be made to rehabilitate degraded paddy soil. This research aims to provide organic matter to determine and rehabilitate its physical properties, Sungai Rakyat Village, Panai Tengah District, Labuhanbatu Regency. This research was conducted in Sungai Rakyat Village, Panai Tengah District, Labuhanbatu Regency with an altitude of ± 8 meters above sea level. This study used a non-factorial Randomized Block Design (RBD) with doses of organic matter (S) City Garbage Compost treatment, which consisted of 5 (five) levels, namely: Control, 1.5% (42.70 tons/ha ), 3% (65.40 tonnes/ha), 4.5% (78.10 tonnes/ha), 6% (104.8 tonnes/ha). Provision of organic fertilizer, namely municipal waste compost as much as 42.70 tonnes/ha to 65.40 tonnes/ha, can improve soil properties in Sungai Rakyat Village, Panai Tengah District so that the soil organic matter content reaches 3%.